Penerapan Metode WASPAS (Weighted Aggregated Sum Product) dan ROC (Rank Oder Centroid) Dalam Penentuan Bimbingan Belajar Terbaik - Juanda Hakim Lubis; Mesran; Fatimah Nadratul Hakim (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Mentoring is a solution that helps to repeat lessons taught at school. The selection of extracurricular lessons includes two factors, namely motivational factors because students choose extracurricular lessons because of low school grades, and consequential motivational factors, students choose extracurricular lessons because of encouragement from outside and invitations from friends. . In determining the best tutoring, a Decision Support System (DSS) is needed. DSS is a solution-based technology system that provides a variety of information to support decision making, both in semi-structured and unstructured situations where there is no certainty about how decisions should be made. To overcome this problem, in this study the authors used the Weighted Aggregation and Product Assessment (WASPAS) method and the Ranked Order Centroid (ROC) method. The WASPAS method performs a ranking process according to attributes with different weights and the ROC method for weighting. The research showed that Bimbel Virgo has the highest priority with a value of 1.093 as the institution of choice in determining the best tutoring, because it gets the highest rating compared to other alternatives